Estimating greenhouse gas emissions from Iran's domestic wastewater sector and modeling the emission scenarios by 2030. (1st November 2019) - Nayeb, Hossein; Mirabi, Maryam; Motiee, Homayoun; Alighardashi, Abolghasem; Khoshgard, Ahmad
Abstract: Domestic and industrial wastewaters are categorized as anthropogenic greenhouse gas emission sources. Wastewater collection systems, wastewater treatment plants and discharging wastewater to the environment lead to direct greenhouse gas (carbon dioxide, nitrous oxide, and methane) emission from biological processes and indirect emissions due to energy consumption. In this study, the current status of greenhouse gas emissions from the domestic wastewater sector in Iran and emission scenarios up to the horizon of 2030 were estimated. According to the developed estimations based on the calculation method presented by Intergovernmental Panel on Climate Change (IPCC) for greenhouse gas emissions, methane (144.94 kt/yr) and nitrous oxide (1.47 kt/yr) are emitted directly in the domestic wastewater sector. Thus, wastewater treatment plants are releasing methane (8.542 kt/yr) and nitrous oxide (0.0273 kt/yr) directly along with carbon dioxide (901.77 kt/yr) indirectly. In the next phase of this study, different scenarios of greenhouse gas emissions from the domestic wastewater sector were developed. According to the calculations, the highest emission will occur in 2030, when the people access to wastewater treatment systems increases, while the performance of the wastewater treatment plants has not been improved (6, 024.46 ktCO2e /yr). Also, the lowest emission will occur when people's access to wastewater treatment systems has increased and the performance of these wastewater treatment plants has been improved at the same time (2, 739.31 ktCO2e /yr). According to the result of this study, the best outline will be achieved if the primary focus is on the improvement of wastewater treatment operation by 2025, and since then the focus shifts forward to increasing population coverage and upgrading performance. Highlights: The population connected to WWTP are causing 36% of GHG emitted from wastewater sector. In Iran's domestic wastewater sector 144.94 kt/yr CH4 and 1.47 kt/yr N2 O are emitted. Different scenarios of greenhouse gas emissions were developed up to 2030. In the worst scenario (2), the highest emission will occur (6, 024.46 ktCO2 e/yr). In the best scenario (4), the lowest emission will occur (2, 739.31 ktCO2 e/yr).